2005
DOI: 10.1093/ndt/gfi253
|View full text |Cite
|
Sign up to set email alerts
|

Update on adverse drug events associated with parenteral iron

Abstract: The frequency of intravenous iron-related ADEs reported to the FDA has decreased, and overall, the rates are extremely low. This is the fourth report suggesting increased risks associated with the provision of higher molecular weight iron dextran. Life-threatening and other ADEs appear to be lower with the use of non-dextran iron formulations, although the cost per ADE prevented is extremely high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
266
2
16

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(296 citation statements)
references
References 17 publications
8
266
2
16
Order By: Relevance
“…The large majority of serious adverse events (SAEs) with iron dextran were due to the HMW formulations, Dexferrum and Imferon. The authors concluded that when HMW iron dextran is avoided, the other formulations are safe with a SAE rate of less than 1:200,000 administrations [43]. This is supported by two published prospective studies and a meta-analysis comparing LMW iron dextran and IS [44][45][46], two prospective comparisons of ferumoxytol and IS [47,48], and a retrospective observational analysis [49], all of which found no significant difference in adverse events among the various formulations.…”
Section: Safety Issuesmentioning
confidence: 86%
“…The large majority of serious adverse events (SAEs) with iron dextran were due to the HMW formulations, Dexferrum and Imferon. The authors concluded that when HMW iron dextran is avoided, the other formulations are safe with a SAE rate of less than 1:200,000 administrations [43]. This is supported by two published prospective studies and a meta-analysis comparing LMW iron dextran and IS [44][45][46], two prospective comparisons of ferumoxytol and IS [47,48], and a retrospective observational analysis [49], all of which found no significant difference in adverse events among the various formulations.…”
Section: Safety Issuesmentioning
confidence: 86%
“…In facts, the medical community experienced a long lasting generalized prejudice against IV iron, whatever the preparation used. Only relatively recently, it was realized that severe and potentially lethal reactions were almost exclusively due to HMWD-iron [99], which, in the meantime, was no longer produced since 1992 [100] and replaced by other preparations (Fig. 3a).…”
Section: Historical Considerationsmentioning
confidence: 99%
“…19 The high-molecular-weight iron dextran formulation most frequently were responsible for these side effects seen in 2.3% of the patients. 20,21 However, the availability of new preparations like iron sucrose, with much better safety profiles, are more useful in day to day clinical practice. 17,22 The present study was done to evaluate the safety and the effectiveness of IV iron sucrose for pre-op patients waiting for fitness prior to surgery.…”
Section: Discussionmentioning
confidence: 99%